Effect of neurovascular bundle sparing radical cystectomy on post‐operative continence and sexual function: A systematic review and meta‐analysis. (30th September 2020) - Xiong, Xingyu; Qiu, Shi; Yi, Xianyanling; Jin, Kun; Xu, Hang; Lei, Hanran; Bai, Shengjiang; Peng, Ge; Yang, Lu; Wei, Qiang
Abstract: Background: It is unclear whether the neurovascular bundle (NVB) sparing could improve post‐operative urinary continence and potency. Furthermore, concern remains regarding the impact of nerve‐sparing (NS) radical cystectomy (RC) on oncological outcomes. Objectives: The primary objective of this meta‐analysis was to evaluate whether in men undergoing NS RC could improve post‐operative urinary continence and potency. The secondary objective was to assess whether NS RC could compromise the oncological control. Materials and methods: A systematic search of the PubMed and Web of Science was performed in February 2020, yielding 1446 unique records. A total of 13 comparative cohort studies were included. Risk of bias in each study was assessed separately by two authors using the Newcastle‐Ottawa Scale (NOS). Results: Data from 921 participants in 12 studies were synthesized in the present meta‐analysis. Meta‐analysis revealed that NS compared with non–nerve sparing (NNS) results in improved post‐operative potency, daytime continence, and nocturnal continence. RRs were 9.35 ( P < .00001) in potency, 1.11 ( P = .045) in daytime continence, and 1.33 ( P = .002) in nocturnal continence, respectively. Furthermore, no differences were found in the included studies reporting oncological outcomes. RRs were 0.88 ( P = .61) in local and/or distant recurrence between two groups. A sensitivity analysis of prospective studies indicated consistent results. Discussion and conclusion: This meta‐analysis indicates that NS RC can improve post‐operative potency, and daytime and nocturnal urinary continence, without compromising oncological control, compared with NNS RC in men.